Global profiling of α-glucosidase inhibitors from Citri Reticulatae Pericarpium based on affinity ultrafiltration screening coupled with UPLC-ESI-Orbitrap-MS method - Hongping Wang; Qiong Yin; Zhaozhou Lin; Quantao Ma; Zhaohua Zhang; Jun Jia (PLoS ONE, 2026)
As a medicinal and edible herb, Citri Reticulatae Pericarpium has multiple biological activities. The latest modern pharmacological researches have found that Citri Reticulatae Pericarpium has the effect of lowering blood sugar, and its extract can inhibit the activity of α-glucosidase. However, which component has inhibitory activity on α-glucosidase and the degree of inhibition are not clear. In order to solve this problem, this study used affinity ultrafiltration screening coupled with UPLC-ESI-Orbitrap-MS method to systematically screen α-glucosidase inhibitors from Citri Reticulatae Pericarpium for the first time. Through affinity ultrafiltration technology, the active components were selected, and through UPLC-ESI-Orbitrap-MS technology, their structures were identified. Finally, total 84 active ingredients were selected as α-glucosidase inhibitors, and most of them were multimethoxy flavonoids. Our results indicated that inhibiting α-glucosidase activity was probably one of the most important mechanisms for Citri Reticulatae Pericarpium exerting its hypoglycemic effect. In addition, our results first reported that multimethoxy flavonoids had the effects of hypoglycemic activity and potential anti-diabetes value.